Fetal growth and subsequent risk of breast cancer: results from long term follow up of Swedish cohort. Issue 7383 (1st February 2003) - McCormack, V A; Silva, I dos Santos; De Stavola, B L; Mohsen, R; Leon, D A; Lithell, H O
Abstract: Objective: To investigate whether size at birth and rate of fetal growth influence the risk of breast cancer in adulthood. Design: Cohort identified from detailed birth records, with 97% follow up. Setting: Uppsala Academic Hospital, Sweden. Participants: 5358 singleton females born during 1915-29, alive and traced to the 1960 census. Main outcome measures: Incidence of breast cancer before (at age <50 years) and after (≥ 50 years) the menopause. Results: Size at birth was positively associated with rates of breast cancer in premenopausal women. In women who weighed ≥4000 g at birth rates of breast cancer were 3.5 times (95% confidence interval 1.3 to 9.3) those in women of similar gestational age who weighed <3000 g at birth. Rates in women in the top fifths of the distributions of birth length and head circumference were 3.4 (1.5 to 7.9) and 4.0 (1.6 to 10.0) times those in the lowest fifths (adjusted for gestational age). The effect of birth weight disappeared after adjustment for birth length or head circumference, whereas the effects of birth length and head circumference remained significant after adjustment for birth weight. For a given size at birth, gestational age was inversely associated with risk (P=0.03 for linear trend). Adjustment for markers of adult risk factors did not affect these findings. Birth size was not associated with rates of breast cancer in postmenopausal women. Conclusions: Size at birth, particularly length and head circumference, is associated with risk of breast cancer in women aged <50 years. Fetal growth rate, as measured by birth size adjusted for gestational age, rather than size at birth may be the aetiologically relevant factor in premenopausal breast cancer.